PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT TERHADAP HASIL BELAJAR SISWA SMK AL-MADANI PONTIANAK - Deas, Ogi; Sahputra, Rachmat; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to apply the Teams Games Tournament (TGT) type of cooperative learning model in order to improve student learning outcomes. This type of research is quantitative, the form of research used is Pre Experimental Design with One Group Pretest-Postest Design. Retrieval of data using instruments in the form of a description test that is tailored to the characteristics of the understanding of the concept and has been tested using content validation and reliability. The results showed that using the TGT type of cooperative learning model could improve student learning outcomes. Based on the results of data analysis in the normality test, the results of both pre-test and post-test values were normal with significant values for pre-test 0.0378 < 0.05, meaning that the data were not normally distributed and significant post-test values 0.184 > 0 05 means the data is normally distributed. In the Wilcoxon Test, the Asymp value was obtained. Sig. (2-tailed) 0,000 < 0.05, then Ho is rejected and Ha is accepted, which states that there is an influence of the TGT (Teams Games Tournament) cooperative learning model on improving the learning outcomes of class X students of TKJ SMK Al-Madani Pontianak on Mol. So, overall the TGT type of cooperative learning model can improve student learning outcomes on mole concept material. Keywords:            Model Cooperative Learning Models, Teams Games Tournament, Learning Outcomes, Mole Concepts.